DOI: 10.18174/388582
|View full text |Cite
|
Sign up to set email alerts
|

Assessing unconsciousness in livestock at slaughter

Abstract: Verhoeven, M.T.W. (2016). Assessing unconsciousness in livestock at slaughter. PhD thesis, Wageningen University, The Netherlands Assessing unconsciousness in livestock at different stages of the slaughter process is a legal requirement according to EU legislation. The assessment can be based on absence of readily observable indicators (behavioural indicators, physical signs and reflexes) or, under experimental conditions, by recording and subsequent assessment of brain activity as presented in an electroencep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 139 publications
(362 reference statements)
0
5
0
Order By: Relevance
“…This is in line with previous studies, such as the work of Fricker and Riek [20], who confirmed that convulsive activity still occurs in cattle with absent brain function (isoelectric EEG). Convulsions result from the failure of higher-level motor control centres in the brain, thus being incompatible with a simultaneously maintained consciousness [18,28,40]. Therefore, the mere presence of movements is not suitable to distinguish between consciousness and unconsciousness [29].…”
Section: Stunning Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with previous studies, such as the work of Fricker and Riek [20], who confirmed that convulsive activity still occurs in cattle with absent brain function (isoelectric EEG). Convulsions result from the failure of higher-level motor control centres in the brain, thus being incompatible with a simultaneously maintained consciousness [18,28,40]. Therefore, the mere presence of movements is not suitable to distinguish between consciousness and unconsciousness [29].…”
Section: Stunning Qualitymentioning
confidence: 99%
“…In studies by Terlouw et al [17], all cattle showed at least one movement after stunning, and post-stun movements by cattle with the spinal cord severed after stunning did not differ from those by cattle on which this manipulation was not performed. Clonic seizures such as reflex-like paddling of the hind limb are signs of a correctly performed bolt stun in cattle [17,18]. This is caused by the lack of inhibition of medullary or spinal reflexes due to the trauma-induced failure of higher-level centres in the brain [19] and also explains the occurrence of the above-mentioned convulsions during a zero-line EEG [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…In a later Swedish study, the stun-to-stick interval was 104 seconds for the MSh and 44 seconds at a stationary-but small-scale-slaughterhouse (Hultgren et al, 2018). The stun-to-stick interval should not be longer than 30 s in mechanically stunned animals, in order to ensure that the animal remains unconscious during bleeding [Grandin and Committee 2013in Verhoeven (2016]. In (un-stunned) ritually slaughtered animals, it is not uncommon for blood to enter the airway of the animals.…”
Section: Hazard Identification and Characterization In Each Phasementioning
confidence: 99%
“…28,29 EEG or electrocorticographic (ECoG) traces are used experimentally to measure trends in electrical brain activity of anaesthetised animals, which may indicate onset and extent of insensibility following slaughter. 18,30 A universally preferred measurable welfare indicator at slaughter is difficult to establish, leading stakeholders to incorporate the full variety reported across the literature when discussing welfare at slaughter. 4,31 To the authors' knowledge, there does not appear to be a previously published structured review of the literature specifically comparing welfare indicators of sheep and/or cattle measured at both stun and non-stun slaughter.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies measure observed signs of unconsciousness such as loss of posture, palpebral and corneal reflexes and absence of rhythmic breathing to indicate welfare 28,29 . EEG or electrocorticographic (ECoG) traces are used experimentally to measure trends in electrical brain activity of anaesthetised animals, which may indicate onset and extent of insensibility following slaughter 18,30 . A universally preferred measurable welfare indicator at slaughter is difficult to establish, leading stakeholders to incorporate the full variety reported across the literature when discussing welfare at slaughter 4,31 .…”
Section: Introductionmentioning
confidence: 99%